Development of the neurotrophic keratopathy questionnaire: qualitative research - Lindsey T. Murray; Julie McCormack; Ioana Grobeiu; Ingela Wiklund; Miriam Kimel; Floortje Van Nooten (SpringerOpen, 2020)
Abstract Background Neurotrophic keratopathy/keratitis (NK) is a rare disease of the cornea that can lead to anatomical loss of the eye. Little is known about the NK experience from the patients' perspective. The objectives of this study were to examine the symptomatic experience and impacts of NK on patients and assess the overall comprehension, relevance, and content validity of a new questionnaire. Methods This was a cross-sectional, qualitative study conducted with NK patients with varying levels of disease severity, recruited from one clinical site. One-on-one interviews using concept elicitation and cognitive interviewing techniques were conducted. Results Fourteen NK patients participated; 64.3% were female (n = 9), mean age was 65.7 ± 13.3, and 14.3% (n = 2), 21.4% (n = 3), and 64.3% (n = 9) were classified as Mackie stage I, stage II, or stage III, respectively. Participants reported 24 concepts, including: redness (n = 12, 86%), sensitivity to light (n = 11, 79%), general discomfort (n = 9, 64%), dry eye (n = 9, 64%), reduced visual acuity (n = 9, 64%), blurred vision (n = 8, 57%), and eye fatigue (n = 8, 57%). No new concepts were reported after the 13th interview. The most frequently reported impacts included frustration (n = 10, 71%), driving impairment (n = 8, 57%), reading impairment (n = 7, 50%), difficulty watching television (n = 7, 50%), and concern with potentially losing their eyesight due to NK (n = 6, 43%). Participants provided positive feedback on the draft NK Questionnaire (NKQ) and felt that it was comprehensive and relevant to their experience with NK. Additionally, the recall period, instructions, item concepts, and response options were well-understood by participants. Minor revisions were made to the tool for consistency (i.e., the timeframe "in the past 7 days" was added to items 12-14); item 14 was modified to include "how often"; examples were added to item 9. Conclusions The results of the concept elicitation portion of the qualitative study support the content validity of the draft NKQ. The clinically significant concepts identified in the literature and raised during concept elicitation are included as items in the questionnaire. Further assessment of the psychometric properties should be conducted in support of this new tool to measure the effect of new treatments on symptoms and impacts associated with NK.